MEDIA PEMBELAJARAN M3 (MEMBACA, MENULIS, MENGHITUNG) BERBASIS MULTIMEDIA UNTUK ANAK USIA DINI - Lalu Puji Indra Kharisma; Khairunnazi; Muh. Fahrurrozi (TEKNIMEDIA: Teknologi Informasi dan Multimedia, 2020)
Kindergarten Education (TK) is a form of early childhood education, namely children aged four to six years. The purpose of kindergarten education is to lay the foundation towards the development of attitudes, knowledge, skills and creativity needed by children to adjust to the environment and their subsequent development into a literacy and numeracy school. To develop basic abilities of early childhood in reading and reading required interesting methods and make children interested in learning, so many books are available in bookstores with various colours and interesting shapes, but sometimes they also need to hear how to pronounce and hear what they learn independently. To develop their interest in learning independently in reading, writing and counting can be done by creating an M3 learning media application (reading, writing, counting) that they can access on a smartphone, with this learning media can make it easier for them to remember what they have heard and seen when accessing these learning media when playing Smartphone.